Agnieszka Gromkowska-Melosik. Femininity as a source of socio-cultural anxieties. Crystallizations and Dispersions. Poznan 2020: Adam Mickiewicz University Press. Pp. 181. - Adamczewski, Jakub (Journal of Gender and Power, 2020)
Review